SELF ESTEEM AND ANXIETY: A CORRELATIONAL STUDY AMONG STUDENTS OF PRIVATE AND GOVERNMENT SCHOOLS (International Journal of Food and Nutritional Sciences, 2022)
Pupils in school deal with a variety of issues, and when they can't handle these issues, anxiety sets in. An uncomfortable sensation of uncertainty about the future that may be transient or prolonged is what is often understood as anxiety. Research has repeatedly shown that school-age children who experience extreme anxiety and low self-esteem are more likely to attempt suicide.This study mainly focuses on self-esteem and anxiety of private and government school students. For this, purpose 80 private school students and 80 government school students of Bihar were purposively selected and they were administered Rosenberg Self-Esteem Scale and Sinha Anxiety Scale. The Pearson’s product moment were applied to analyze the data. The results as follows: A significant negative relationship between self-esteem and anxiety of private school students was obtained. A significant negative relationship between self-esteem and stress of government school students was work out. The study aims in making the students and their parents to aware of the various stressors and the different coping strategies that can help them deal with the stressors in a better way, and thus maintaining their self-esteem. The review concludes with a summary of major research findings, as well as a consideration of future directions and implications for practice and policy.